'Here, the girl has to obey the family's decision': A qualitative exploration of the tactics, perceived perpetrator motivations, and coping strategies for reproductive coercion in Bangladesh - Erin E. Pearson; Fahima Aqtar; Dipika Paul; Jamie L. Menzel; Ruvani W. Fonseka; Jasmine Uysal; Kathryn L. Andersen; Jay G. Silverman (Elsevier, 2023)
Reproductive coercion (RC) undermines women's decision-making in reproductive health and negatively impacts women's health and well-being. This qualitative study explored RC in Bangladesh using in-depth interviews (IDIs) and focus group discussions (FGDs) with violence support centre clients, menstrual regulation (MR) and postabortion care (PAC) clients, and MR/PAC providers and pre- and post-procedure counsellors. All IDIs and FGDs were audio recorded, transcribed verbatim, and translated from Bangla to English for thematic analysis. RC was perpetrated primarily by male partners and in-laws and included both pregnancy-promoting tactics (such as contraceptive sabotage and forced continuation of an unwanted pregnancy) and pregnancy-preventing tactics (such as forced contraceptive use and forced MR). Threats and violence were tactics used for pregnancy-promoting and pregnancy-preventing RC. Perceived motivations for RC perpetration included family formation or dissolution, son preference, and a desire to maintain power or control over a woman. The primary motivator for contraceptive sabotage was concern about the safety and side effects of contraception, rather than pregnancy promotion. We classify this as contraceptive-related coercive control rather than RC due to the lack of pregnancy promoting intent. Women's responses to RC and contraceptive-related coercive control ranged from capitulation to active coping strategies such as covert use of contraception and MR, and enlisting providers' help to avoid forced MR. Differences in motivation for perpetration of RC and contraceptive-related coercive control call for distinct intervention strategies to support women's reproductive autonomy.